Tamaño, estructura y distribución de una población de Crocodylus acutus (Crocodylia:Crocodilidae) en Costa Rica - Sasa, Mahmood (1992)
Spatial distribution and population size of Crocodylus acutus were estimated during the dry season (January-April) of 1989 and 1990 in the Grande de Tárcoles rivet, SO Co sta Rica. A high den síty ( 19.1 índividuals/km) was foond,with no dífference between years. The síze-class distribution was 43.9% juvenile, 21.3% sub-adWt and 34.8% adulto Similar results have been reponed from other parts of its range